Electrocardiogram as a predictor of sudden cardiac death in middle-aged subjects without a known cardiac disease - Henri K. Terho; Jani T. Tikkanen; Tuomas V. Kenttä; Juhani M. Junttila; Aapo L. Aro; Olli Anttonen; Tuomas Kerola; Harri A. Rissanen; Paul Knekt; Heikki V. Huikuri (International Journal of Cardiology: Heart & Vasculature, 2018)
Background: Abnormal 12‑lead electrocardiogram (ECG) findings and proposing its ability for enhanced risk prediction, majority of the studies have been carried out with elderly populations with prior cardiovascular diseases. This study aims to denote the association of sudden cardiac death (SCD) and various abnormal ECG morphologies using middle-aged population without a known cardiac disease. Methods: In total, 9511 middle-aged subjects (mean age 42 ± 8.2 years, 52% males) without a known cardiac disease were included in this study. Risk for SCD was assessed after 10 and 30-years of follow-up. Results: Abnormal ECG was present in 16.3% (N = 1548) of subjects. The incidence of SCD was distinctly higher among those with any ECG abnormality in 10 and 30-year follow-ups (1.7/1000 years vs. 0.6/1000 years, P < 0.001; 3.4/1000 years vs. 1.9/1000 years, P < 0.001). At 10-year point, competing risk multivariate regression model showed HR of 1.62 (95% CI 1.0–2.6, P = 0.05) for SCD in subjects with abnormal ECG. QRS duration ≥ 110 ms, QRST-angle > 100°, left ventricular hypertrophy, and T-wave inversions were the most significant independent ECG risk markers for 10-year SCD prediction with up to 3-fold risk for SCD. Those with ECG abnormalities had a 1.3-fold risk (95% CI 1.07–1.57, P = 0.007) for SCD in 30-year follow-up, whereas QRST-angle > 100°, LVH, ER ≥ 0.1 mV and ≥0.2 mV were the strongest individual predictors. Subjects with multiple ECG abnormalities had up to 6.6-fold risk for SCD (P < 0.001). Conclusion: Several ECG abnormalities are associated with the occurrence of early and late SCD events in the middle-age subjects without known history of cardiac disease. Keywords: Sudden cardiac death, Risk prediction, Electrocardiogram, Follow-up studies